Sosialisasi kepada Masyarakat Spazio mengenai Pentingnya Melek Investasi di Zaman Sekarang - Andrew Baihaqi Firdaus; Mei Retno Adiwaty (Universitas Muhammadiyah Manado, 2023)
In this modern era dominated by rapid economic and financial changes, it is important for individuals to have a good understanding of investing and take an active role in managing their finances. Investment is an activity or act of buying or placing funds or assets into financial instruments or other assets with the aim of obtaining the expected return or yield in the future. Investing generally involves risk evaluation, market analysis and decision making based on a deep understanding of the investment instrument and long-term financial goals. With increased investment awareness, individuals can optimize their financial potential, manage risk effectively, and achieve long-term financial goals. As a result, it is hoped that this outreach will encourage the people of Spazio to become more investment literate, making them better prepared to face the challenges and opportunities in today's financial world